PENGARUH HARGA, INOVASI PRODUK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA IKM KERAJINAN LOGAM DI KECAMATAN CITEUREUP KABUPATEN BOGOR (Studi Pada CV.Wasilah Agung Prakarsa) - Dinda Anggraini; Sudarijati; Titiek Tjahja Andari (Universitas Djuanda, 2022)
The purchase decision is an important things that will. affect the achievement of companys goal. The purpose of this research is to see the effect of price, product iinnovation, and product quality on purchasing decisions. The method used is multiple linear regression analysis. The sampling technique in this study is saturated sampling. The sample used is all consumers who are resellers totaling 100 people. The results of this research is simultaneously and partially the variables of price, iproduct innovation, and product quality had a positive and significant effect on purchasing decisions at CV. Wasilah Agung Prakarsa. Keywords: Price, Product Innovation, Product Quality, Purchase Decision